Immune-related adverse events with PD-1/PD-L1 inhibitors: insights from a real-world cohort of 2523 patients - Yan, Ting; Long, Minghui; Liu, Chaoyi; Zhang, Jiwen; Wei, Xingyu; Li, Fei; Liao, Dehua (Frontiers in Pharmacology, 2025)
PurposeImmune checkpoint inhibitors (ICIs) have significantly changed cancer therapy, improving patient survival rates and clinical outcomes. Nevertheless, the use of PD-1/PD-L1 inhibitors can result in immune-related adverse events (irAEs). This study aims to investigate the prevalence and associated risk factors of irAEs in a real-world setting, as well as to assess their effects on optimal therapeutic outcomes.MethodsA retrospective analysis involved 2523 patients with cancer who received inpatient PD-1/PD-L1 inhibitors treatment between January 2018 and December 2022. We documented patients’ demographic and clinical characteristics, PD-1 or PD-L1 inhibitors, treatment modalities, incidences, timing, and severity of irAEs, and efficacy outcomes by reviewing inpatient records. Patients were categorized into an irAEs group and a non-irAEs group, with the former further subdivided into a multiple irAEs group and a single irAE group. Chi-square tests were employed to evaluate differences in baseline characteristics and efficacy outcomes between the irAEs and non-irAEs groups, as well as between the multiple and single irAE groups. Additionally, logistic regression analysis was utilized to identify risk factors linked to irAEs.ResultsAmong 2523 eligible patients, 1096 reported 1802 irAEs, with an incidence incidence of 43.4%. Among 1096 individuals, 92.1% were classified as grade 1–2, while 7.9% were grade 3 or higher. IrAEs affected various organ systems, with endocrine toxicity (17.7%), hepatic toxicity (17.2%), and hematologic toxicity (11.4%) being the most common. 20.5% patients experienced multi-system irAEs. The average time for patients to develop irAEs was within four treatment cycles. Significant differences in patient gender, age, Eastern Cooperative Oncology Group (ECOG) Performance Status (PS), comorbidities, PD-1 or PD-L1 inhibitors, and treatment modalities were observed between the irAEs and non-irAEs groups, but not between the multiple irAEs and single irAE groups. Compared to the non-irAEs group, the irAEs group exhibited a higher objective response rate (ORR) and disease control rate (DCR), and the multiple irAEs group also showed a higher ORR than the single irAE group.ConclusionThis real-world study indicated that the occurrence of irAEs is related to patient gender, age, ECOG PS, comorbidities, PD-1/PD-L1 inhibitors, and treatment modalities. The occurrence of irAEs may be associated with better treatment benefits.